Maintaining intraoperative normothermia reduces blood loss in patients undergoing major operations: a pilot randomized controlled clinical trial - Yi, Jie (BMC Anesthesiol, 2018)
BACKGROUND: Inadvertent intraoperative hypothermia (core temperature < 36 °C) is a common but preventable adverse event. This study aimed to determine whether active intraoperative warming reduced bleeding in patients undergoing major operations: open thoracic surgery and hip replacement surgery. METHODS/DESIGN: The study was a pilot, prospective, parallel two-arm randomized controlled trial. Eligible patients were randomly allocated to two groups: passive warming (PW), with application of a cotton blanket (thermal insulation), or active warming (AW), with a forced-air warming system. The primary endpoint was intraoperative blood loss, and secondary endpoints were surgical-site infection, cardiovascular events, and length of stay in the post-anesthesia care unit, intensive care unit, and hospital. RESULTS: Sixty-two patients were enrolled. Forced-air active warming maintained intraoperative normothermia in all AW subjects, whereas intraoperative hypothermia occurred in 21/32 (71.8%) of PW patients (p = 0.000). The volume of blood loss was more in the PW group (682 ± 426 ml) than in the AW group (464 ± 324 ml) (p < 0.021), and the perioperative hemoglobin value declined more in the PW group (28.6 ± 17.5 g/L) than in the AW group (21.0 ± 9.9 g/L) (p = 0.045). However, there were no difference in other clinical outcomes between two groups. CONCLUSION: Intraoperative active warming is associated with less blood loss than passive warming in open thoracic and hip replacement operations in this pilot study. TRIAL REGISTRATION: This trial was registered with Clinicaltrials.gov (Identifier: NCT02214524) on 27 August 2014.